Sociodemographic and obstetric factors related to low birth weight in the context of early pregnancy - Brenda Karoline Santos; Viviane Macedo Marinho Barreto; Vinícius Souza Santos; Neyana Maria Coelho de Souza Prado; José Rodrigo Santos Silva; Ana Jovina Barreto Bispo; Andrea Ferreira Soares
Abstract Objectives: to analyze sociodemographic and obstetric factors that may influence the occurrence of low birth weight in the context of early pregnancy. Methods: the sample consisted of 232 pregnant teenagers, aged 10-19 years old, were assisted at a public maternity hospital in Aracaju-SE during the period of August 2012 to July 2016. The data collection was conducted through a structured questionnaire. Results: low birth weight was observed in 41.38% of the newborns and there was a statistical association between the educational level and the marital status with the occurrence of low birth weight in newborns among teenage mothers, with p=0.0286 and p=0.0247, respectively. Conclusions: the socioeconomic factors may contribute to the occurrence of low birth weight in newborns of teenage mothers and teenage pregnancy at this age represents a serious public health problem.